Centralization and Decentralization in Mainland China's Agriculture, 1949-1962 - Perkins, Dwight H. (Quarterly Journal of Economics, 1964)
Introduction, 208. — Price policy, 1950–53, 209. — Introduction of compulsory quotas, 1954–55, 216. — Centralization through cooperatives, 1956–57, 219. — Communes and anarchy, 1958–59, 227. — Revisions, 1960–62, 232. — Centralization versus decentralization, 235.